Volume 2A: Turbomachinery 2018
DOI: 10.1115/gt2018-76597
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Analysis of Unsteady Flow Structure in a Centrifugal Compressor With Variable Vaned Diffuser

Abstract: The unsteady flow at small flow rates is always the most important of typical unsteady phenomena in centrifugal compressors, since it is closely related to the operating safety and efficiency. To study the mechanism of stall and surge generation, an experimental research on an industrial centrifugal compressor with variable vaned diffuser is carried out to study the unsteady flow structure from design point to surge. A multi-phase dynamic pressure measurement is conducted, based on 23 dynamic pressure sensors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The flow decomposition technique is used to distinguish different flow patterns that occur within a compressor. POD and DMD methods are commonly applied to pressure fields to study the internal flow of fluid machinery in the literature [25][26][27][28][29]. The modal decomposition methods are suitable for the study of pressure loss and flow instability caused by stall cell and impeller-diffuser interaction near the shroud side of the diffuser.…”
Section: Flow Field Modal Decompositionmentioning
confidence: 99%
See 1 more Smart Citation
“…The flow decomposition technique is used to distinguish different flow patterns that occur within a compressor. POD and DMD methods are commonly applied to pressure fields to study the internal flow of fluid machinery in the literature [25][26][27][28][29]. The modal decomposition methods are suitable for the study of pressure loss and flow instability caused by stall cell and impeller-diffuser interaction near the shroud side of the diffuser.…”
Section: Flow Field Modal Decompositionmentioning
confidence: 99%
“…The pressure field for DMD modes of these two frequencies at 0.95 span is shown in Figure 22. Similar to the POD method, the DMD method is time-dependent, which describes the evolution characteristics of the vortex structures at a specific frequency during a period [29]. It can be seen from Figure 22a that the pressure fluctuation caused by the stall cells mainly appears in the diffuser passages, especially in the TVD, where the largescale vortex structures block part of the diffuser passages.…”
Section: Flow Field Modal Decompositionmentioning
confidence: 99%
“…The results show that the compressed DMD approach can save 88.4% of the calculation time, and it is found that the origin of the diffuser stall lies at the hub surface with a fixed circumferential position near the diffuser outlet. To visually show the influence of impeller clearance vortex and separation vortex on the internal flow of vaned diffuser, the flow mechanism in the compressor was studied by the POD and DMD method [29]. Previous studies have successfully placed and characterized the coherent flow structures in the compressor stage under the stall condition by using the POD and DMD method [30].…”
Section: Introductionmentioning
confidence: 99%
“…Unstable flow phenomena, like stall and surge, has always been a hot topic in the industry of compressors, but so far there are still many unresolved issues [1,2]. In the recent researches on centrifugal compressors, an insight into the internal unstable flow structure, especially at the tip clearance, played an important role in improving the stability of the overall machine [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%